2017
DOI: 10.3390/app7080777
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Proactive Resource Provisioning in IaaS Clouds

Abstract: Abstract:Cloud computing is an emerging technology for rapidly provisioning and releasing resources on-demand from a shared resource pool. When big data is analyzed/mined on the cloud platform, the efficiency of resource provisioning would affect the system performance. This work proposes a framework for proactive resource provisioning in IaaS (Infrastructure as a Service) clouds to improve system performance. The proposed framework consists of the virtual cluster computing system, the profiling system, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To further substantiate our claims, we compare our methods with existing studies as shown in Table 3. This table contrasts our AI-driven approach with other methodologies, such as the human-monitored trial-error approach proposed by Lee et al (2017) [2] and the dynamic Johnson sequencing algorithm by Banerjee et al (2023) [3], emphasizing the unique benefits of real-time AI optimization without human intervention.…”
mentioning
confidence: 89%
“…To further substantiate our claims, we compare our methods with existing studies as shown in Table 3. This table contrasts our AI-driven approach with other methodologies, such as the human-monitored trial-error approach proposed by Lee et al (2017) [2] and the dynamic Johnson sequencing algorithm by Banerjee et al (2023) [3], emphasizing the unique benefits of real-time AI optimization without human intervention.…”
mentioning
confidence: 89%
“…The main reason is the properties of each resource are too simple and crude to manage and schedule; furthermore, these distributed heterogeneous resources are always used in different manners. Thus, one main step for this work is to establish a general schedulable model that encapsulates diverse distributed resources with the idea of Infrastructure as a Service (IaaS) [50]. On this basis, it is necessary to establish relevant task planning and execution mechanisms.…”
Section: Virtualized-service and Event Based Cooperation Architecturementioning
confidence: 99%
“…In PaaS, a platform for users is provided for programs, such as the Google APP Engine, one kind of PaaS platform. In the last type of service, the IaaS, the user can rent the hardware resources to build their own framework, such as a Cloud server [2][3][4]6]. No matter what kind of cloud service is applied to the cloud computing network, there is a common character: each cloud server has different capabilities and computing abilities.…”
Section: Introductionmentioning
confidence: 99%